Enrichment of copper and recycling of cyanide from copper–cyanide waste by solvent extraction - Gao, Teng-yue; Liu, Kui-ren; Han, Qing; Xu, Bin-shi (International journal of minerals, metallurgy and materials, 2016)
The enrichment of copper from copper–cyanide wastewater by solvent extraction was investigated using a quaternary ammonium salt as an extractant. The influences of important parameters, e.g., organic-phase components, aqueous pH values, temperature, inorganic anion impurities, CN/Cu molar ratio, and stripping reagents, were examined systematically, and the optimal conditions were determined. The results indicated that copper was effectively concentrated from low-concentration solutions using Aliquat 336 and that the extraction efficiency increased linearly with increasing temperature. The aqueous pH value and concentrations of inorganic anion impurities only weakly affected the extraction process when varied in appropriate ranges. The CN/Cu molar ratio affected the extraction efficiency by changing the distribution of copper–cyanide complexes. The difference in gold leaching efficiency between using raffinate and fresh water was negligible.